A Bayesian Network Concept for Pain Assessment - Sadik, Omowunmi; Schaffer, J David; Land, Walker; Xue, Huize; Yazgan, Idris; Kafesçiler, Korkut; Sungur, Mürvet (JMIR Publications Inc., 2022)
In this study, we propose an approach that provides a useful data summary related to a patient’s experience of pain. Because pain is a very important but subjective phenomenon that currently has no calibratable method for assessing it, we suggest an approach that uses calibratable biomarker sensors with the patient’s self-assessment of perceived pain. We surmise that such an approach may only be able to clearly distinguish between cases in which the available evidence is consistent. However, this information may provide clinicians with valuable insights, and as research progresses into how biomarkers are related to pain, more specific insights may emerge regarding how specific evidence inconsistencies may point to particular pain causes. We provide a brief overview of pain science, including the types of pain, contemporary pain theories, pain, and pain assessment techniques. Next, we present novel approaches to pain sensor development, including an overview of research on pain-related biomarker sensors and artificial intelligence methods for summarizing the evidence. We then provide some illustrations of the implementation of our approach. Some specifics are presented in the Methods section of this paper. For example, in a set of 379 patients, we observed 80% evidence of consistency and 5 types of inconsistencies. Information regarding the gender and individual differences in cyclooxygenase-2 and inducible nitric oxide synthase data on reported pain could contribute to the inconsistency. Different causes of inconsistencies are also attributed to cultural or temporal variability of cyclooxygenase-2 and inducible nitric oxide synthase (as well as their serum variation and half-life), visual analog scale, and other tools. We emphasize that this presentation is illustrative. Much work remains to be done before implementing and testing this approach in a clinically meaningful context.
Keywords: Medical technology; R855-855.5; 3. Good health